TAF1B depletion leads to apoptotic cell death by inducing nucleolar stress and activating p53-miR-101 circuit in hepatocellular carcinoma - Chen, Hang-fei; Gao, Dan-dan; Jiang, Xin-qing; Sheng, Hao; Wu, Qi; Zheng, Quan; Zhai, Qiao-cheng; Yuan, Lei; Liu, Ming; Xu, Li-feng; Qian, Mao-xiang; Xu, Heng; et al. (Frontiers in Oncology, 2023)
Background TAF1B (TATA Box Binding Protein (TBP)-Associated Factor) is an RNA polymerase regulating rDNA activity, stress response, and cell cycle. However, the function of TAF1B in the progression of hepatocellular carcinoma (HCC) is unknown. Objective In this study, we intended to characterize the crucial role and molecular mechanisms of TAF1B in modulating nucleolar stress in HCC. Methods We analyzed the differential expression and prognostic value of TAF1B in hepatocellular carcinoma based on The Cancer Genome Atlas (TCGA) database, tumor and paraneoplastic tissue samples from clinical hepatocellular carcinoma patients, and typical hepatocellular carcinoma. We detected cell proliferation and apoptosis by lentiviral knockdown of TAF1B expression levels in HepG2 and SMMC-7721 cells using clone formation, apoptosis, and Western blotting (WB) detection of apoptosis marker proteins. Simultaneously, we investigated the influence of TAF1B knockdown on the function of the pre-initiation complex (PIC) by WB, and co-immunoprecipitation (Co-IP) and chromatin immunoprecipitation (ChIP) assays verified the interaction between the complexes and the effect on rDNA activity. Immunofluorescence assays measured the expression of marker proteins of nucleolus stress, fluorescence in situ hybridization (FISH) assays checked the rDNA activity, and qRT-PCR assays tested the pre-rRNA levels. Regarding molecular mechanisms, we investigated the role of p53 and miR-101 in modulating nucleolar stress and apoptosis. Finally, the impact of TAF1B knockdown on tumor growth, apoptosis, and p53 expression was observed in xenograft tumors. Result We identified that TAF1B was highly expressed in hepatocellular carcinoma and associated with poor prognosis in HCC patients. TAF1B depletion modulated nucleolar stress and apoptosis in hepatocellular carcinoma cells through positive and negative feedback from p53-miR-101. RNA polymerase I transcription repression triggered post-transcriptional activation of miR-101 in a p53-dependent manner. In turn, miR-101 negatively feeds back through direct inhibition of the p53-mediated PARP pathway. Conclusion These findings broaden our comprehension of the function of TAF1B-mediated nucleolar stress in hepatocellular carcinoma and may offer new biomarkers for exploring prospective therapeutic targets in HCC.